Asthma dissemination around patient-centered treatments in North Carolina (ADAPT-NC): a cluster randomized control trial evaluating dissemination of an evidence-based shared decision-making intervention for asthma management. (3rd October 2019) - Ludden, Thomas; Shade, Lindsay; Reeves, Kelly; Welch, Madelyn; Taylor, Yhenneko J.; Mohanan, Sveta; McWilliams, Andrew; Halladay, Jacqueline; Donahue, Katrina; Coyne-Beasley, Tamera; Dolor, Rowena J.; Bray, Paul; et al.
Abstract: Objective : To compare three dissemination approaches for implementing an asthma shared decision-making (SDM) intervention into primary care practices. Methods : We randomized thirty practices into three study arms: (1) a facilitator-led approach to implementing SDM; (2) a one-hour lunch-and-learn training on SDM; and (3) a control group with no active intervention. Patient perceptions of SDM were assessed in the active intervention arms using a one-question anonymous survey. Logistic regression models compared the frequency of asthma exacerbations (emergency department (ED) visits, hospitalizations, and oral steroid prescriptions) between the three arms. Results : We collected 705 surveys from facilitator-led sites and 523 from lunch-and-learn sites. Patients were more likely to report that they participated equally with the provider in making the treatment decision in the facilitator-led sites (75% vs. 66%, p = 0.001). Comparisons of outcomes for patients in the facilitator-led ( n = 1, 658) and lunch-and-learn ( n = 2, 613) arms respectively vs. control ( n = 2, 273) showed no significant differences for ED visits (Odds Ratio [OR] [95%CI] = 0.77[0.57–1.04]; 0.83[0.66–1.07]), hospitalizations (OR [95%CI] = 1.30[0.59–2.89]; 1.40 [0.68–3.06]), or oral steroids (OR [95%CI] =0.95[0.79–1.15]; 1.03[0.81–1.06]). Conclusion : Facilitator-led dissemination was associated with a significantly higher proportion of patients sharing equally in decision-making with the provider compared to a traditional lunch-and-learn approach. While there was no significant difference in health outcomes between the three arms, the results were most likely confounded by a concurrent statewide asthma initiative and the pragmatic implementation of the intervention. These results offer support for the use of structured approaches such as facilitator-led dissemination of complex interventions into primary care practices.